Anda di halaman 1dari 12

Map Scale

- 1km = 1000m = 100000cm


- 1km = 1000000m =10000000000cm
Direct Proportion
-y = kx , where k is a constant
-The graph of y=kx is a straight line passing through the origin.
-The more you buy, the more you pay

Example (1) :
The following table shows the travelling time of (t hours) and
distance covered (y km) by a car.
Travelling
time (t
hours)
Distance
covered
(y km)

0.5

1.0

1.5

2.0

2.5

30

60

90

120

150

(a) Show that t and y are in direct proportion.


t
0.5
1.0
1.5
y
30
60
90
y/t
60
60
60

2.0
120
60

2.5
150
60

Since y/t = 60 is a constant, t and y are in direct proportion.


Example (2):
Given that y is directly proportion to x and y = 30 for a particular
value of x. Find the value of y when x is halved.
y = kx
30 = kx -------------------- Equation 1
y = k(x)(1/2 )
k (x / 4)
kx ---------------------Equation 2
y = (30)
= 7.5

Example (3):
The braking distance of a car is directly proportional to the square of
its speed. When the speed is p metres per second, the braking
distance is 6m. When the speed is increased by 300 %, find
a) an expression for the speed of the car
b) the braking distance,
c) the percentage increase in the braking distance
a) Let Braking distance be D metres
Let Speed be s metres per second
D = ks
s = 100 %
4s = 300% + 100%
D = k(4s)
D = k16s
The expression for the speed of the car is Dk16s
b) D = k16s
When the speed is p metres per second, braking distance = 6m.
D = ks
6 = kp
D = 16kp
16 x 6 = 16kp
16 x 6 = 96
Therefore, the braking distance is 96m.
c) 90/6 x 100% = 1500%

Therefore, the percentage increase is 1500%.

Example (4) :
The volume of a sphere, V cm , is directly proportional to the
cube of its radius, r cm. When the radius increased by 50%, find
the percentage increase in the volume of the sphere.
V = 4.19r

Amount of increase in r = 50% of r


= 50/100 x r
=0.5r
New r = 1r + 0.5r = 1.5r
New volume = New V = 4.19 (1.5r)
= 14.14125r
14.14125r - 4.19r = 9.95125r
Percentage increase = 9.95125r / 4.19r x 100% = 237.5 %

Inverse proportion
- xy = k, where k is constant
- The more people, the lesser time
The lesser people, the more time

Example (1):
A car travels uniformly from A to B. The following table shows the
time take (t hours) at various speeds (v km/h).
Speed
(v
20
40
50
80
100
120
km/h)
Time
taken (t
10
5
4
2.5
2
hours)
1.667
a) Show that t and v are in inverse proportion.
v
t
vt

20
10
200

40
5
200

50
4
200

80
2.5
200

100
2
200

120
1.667
200

In the above table, vt = 200 is a constant. Hence, t and v are in


inverse proportion.
Example (2):
Given that y is inversely proportional to 2x and y = 30 for a
particular value of x. Find the value of y when x is tripled.
y = k/2x
30 = k/2x ------------------------- equation 1
y = k/3(2x)
y = k/6x
y = 1/3 (k/2x) --------------------equation 2
y = 1/3 (30)
= 10

Simple Algebraic Fractions


Expansion
- (a+b) = a + 2ab + b
- (a-b) = a - 2ab + b
- (a+b)(a-b) = a + b
Example (1):
Evaluate each of the following, using special products of algebraic
expressions.
a) 103 = (100+3)
= 100 + 2(100)(3) + 3
= 10000 + 600 + 9
= 10609
b) 301 x 299 = (300+1) x (300-1)
= 300 - 1
= 90000 1
= 89999
Factorisation
Factorise by 1) common term
2) Grouping (involve 4 term)
3) Using (a+b)(a-b) = (a) (b)
a + 2ab + b = (a+b)
a - 2ab + b = (a-b)
4) Cross method
Example (1):
Find the value of each of the following by factorization.
a) 200.5 - 199.5 = (200.5-199.5)(200.5+199.5)
= (1)(400)
= 400
= 20
b) (a + 3b) - (2c + d) = [(a + 3b)-(2c + d)][(a + 3b)+(2c+d)]
= [ a + 3b - 2c - d ][a + 3b + 2c +d]
c) z (x) - 625 = (z) - (25)
= ( z - 25) (z + 25)
= ( z-5)(z + 5)(z + 5) = (z-5)(z+5xz+ 25)
d) x - 4xy 4y -4 = ( x-2y)(x 2y) - 2
= ( x-2y-2)(x-2y+2)
e) A ball is thrown from the top of a building. Its vertical height H
(in m) above the ground at time t seconds during the flight is
given by the formula, H = 90 + 15t 5t.
Find the height of the building.
t=0

H = 90+15(0)-5(0)
= 90m
Changing the subject of a formula
- In the formula, A = 0.5(a+b)h,
A is the subject of the formula. (It is the letter on the left on the
equation)
Must include if there is .
Example (1):
Make h the subject in
S=rh+r
S=r(h+r)
S/ r = h + r
S/ r - r = h
S/ r - r = h
h = S/ r - r
Example (2):
Make V the subject
1/u + 1/v = 1/f
fv/fuv + fu/fuv = vu/fuv
fv + fu
= vu
fv vu
= -fu
v(f-u)
= -fu
v
= -fu/f-u
Example (3):
Make g the subject
T = 2 L/g
T = 4 (L/g)
T/4 = L/g
Tg = 4 L
g = 4 L/T
Multiplication and Division of Algebraic Fractions
- (P/Q) X ( R/S) = PR/QS
- ( P/Q) / (R/S) = P/ Q x S/R
= PS/QR
Addition and Subtraction of Algebraic Fractions
-First find the denominators of individual fractions in an expression.
-Expand each fraction in the given expression to an equivalent one
with the denominator.
Example (1):
a)a-b/1 + (2ab/a-b) = (a b) /a-b + 2ab/a-b
= a +b -2ab+2ab/a-b

=a + b/a-b
Example (2):
a)2x/x+3 5x-1/2x-6 = 2x/x+3 (5x-1/2(x-3))
=2x(2)/2(x-3) (5x-1/2(x-3))
=4x/2(x-3) 5x+1/2(x-3)
= 1-x/2(x-3)
Similarity and Congruency
Congruency
Two figures are congruent if they have the same shape and
sixe,
- all corresponding angles are equal
- all corresponding sides are equal
Congruent Triangles are like twin, they are exactly the same in
term of shapes and sizes.
Below are the methods of identifying them
-SSS
All sides of the two triangles must be exactly the same
-SAS
2 sides and 1 included angle must be the same
-AAS
2 adjacent angles and 1 side must be the same
-RHS
1 right angle, 1 hypotenuse and 1 side must be the same
Similarity
Two figures are similar if they have the same shape but
different sizes,
- all their corresponding angles are equal
- all the ratios of their corresponding sides are equal
Scale Factor
If it is enlargement, the answer will be more than 1.
If it is reduction, the answer will be less than 1.
Example (1):
ABCD is similar to PQRS. The scale factor is enlarging ABCD TO
PQRS is
PQ/AB or QR/BC or RS/CD or SP/DA.
Example (2):
ABCD is similar to PQRS. The scale factor is reducing ABCD TO PQRS
is
AB/PQ or BC/QR or CD/RS or DA/SP.
Scale Drawing

The scale of a drawing is 1:n if 1 cm on the drawing


represents n cm on the actual object.

Linear Equations in Two Unknowns


Solving Simultaneous Equations by Substitution Method
If x=3y-2 and 4x-y=-19
x=3y-2--------------------------------Equation (1)
4x-y=-19-----------------------------Equation (2)
Sub equation (1) into equation (2)
4(3y-2)- y = -19
12y -8 y = -19
11y
=-19+8
11y
=-11
y
= -1
Use y=-1
x
= 3(-1)-2
= -5
Solving Simultaneous Equations by Elimination Method
If 3x + y = -12 and 4x + 5x = -38
3x + y = -12 --------------------------Equation (1)
4x + 5x = -38 ------------------------- Equation (2)
Multiply Equation (1) by 5
15x + 5y = -60-------------------------Equation (3)
Subtract equation 2 from equation 3
15+5y-(4x+5y)=-60-(-38)
11x + 0y = -60-(-38)
11x
= -22
x
= -2
Sub x=-2 into equation (1)
3x + y = -12
3(-2)+y = -12
-6+y = -12
y=-12+6
=-6
Therefore, x=-2, y=-6
If 4x-3y=-23 and 7x+3y=1
4x-3y=-23-------------------------------Equation (1)
7x+3y=1--------------------------------- Equation (2)
Add equation (1) to equation (2)
(4x+3y) + (7x+3y) = -23+1
11x = -22
x
= -2

Sub x=-2 into equation 1 to find y


7(-2)+3y=1
-14+3y=1
3y = 14+1
3y = 15
y = 15/3
=5
If 5x-4y = -56 and 9x-4y=-83
5x-4y = -56--------------------------------equation(1)
9x-4y=-83---------------------------------equation(2)
Subtract eqn 1 from eqn 2
(9x-4y)-(5x-4y) = -83-(-56)
9x-5x-4y+4y = -27
4x = -27
x = -6.75
What if you encounter simultaneous equations that have fraction?
Take note that the steps for the above 2 methods still work except
for 2 additional steps
Additional step 1:
Change all terms in the same equation to the same denominator
Additional step 2:
Cancel all denominators
After the execution of the above 2 steps, follow all the steps that are
listed for the elimination and substitution method above.
x/5 y/4 = 1/3---------------------------equation (1)
x/2 y/3 = 5/6---------------------------equation (2)
4x-5y/20 = 1/3
12x-15y=20-------------------------------equation (3)
3x/6 + 2y /6 = 5/6
3x + 2y = 5---------------------------------equation (4)
Multiply equation (4) by 4 to get 12x
12x + 8y = 20 ----------------------------- equation (5)
Subtract eqn 5 from eqn 3
12x-15y (12x+8y) = 20-20
-15y-8y = 0
-23y =0
y
= 0/-23
=0
Sub y=0 into equation 4 to find x
3x+2(0) = 5
3x = 5
x = 5/3 = 1 2/3
Number of Solution for a Pair of Simultaneous Linear
Equations

Solving Problems using Simultaneous Equations Example (1): The


perimeter of are rectangle is 114cm. The total length of three of its
sides is 93cm.
Find the dimensions of the rectangle.
Let x be the length of the rectangle
Let y be the breadth of the rectangle
x+x+y+y=114
2x+2y = 114 --------------- Equation (1)
2y + y = 93 ----------------- Equation (2)
Subtract eqn 2 from eqn 1
2x+2y-2x-y= 114-93
y = 21
Use equation 2 to find x
2x + y = 93
2x + 21 = 93
2x = 93-21
x = 72/2
= 36 (length)
36cm by 21cm
Example (2): A fraction is equivalent to 1/3 if its numerator
decreases by 2 and its denominator increases by 5. When its
numerator is doubled and 3 is subtracted from its denominator, the
fraction becomes 8/5. Find the original fraction.
Let the numerator be x
Let the denominator by y
x-2/y+5 = 1/3
3x-6 = y+5
3x-y = 6+5
3x y = 11 -------------------------------------Eqn 1
2x/y-3 = 8/5
10x =8y-24
10x-8y =-24 ----------------------------------Eqn 2
Multiply eqn 1 by 8
24x 8y = 88--------------------------------eqn 3
Subtract eqn 2 from eqn 3
24x-8y-10x+8y = 88-(-24)

14x= 112
x=8
Use equation 1 to find y
3x-y=11
3(8)-y =11
-y =11-24
-y =-13
y =13
x/y = 8/13
Steps involves in problem-solving with simultaneous linear
equations in two unknowns as follows:
- Read the question carefully and identify and two unknown
quantities to be
found.
- Use letters, say x and y, to represent the two unknown quantities.
-Express some other quantities in the problem in terms of x and y.
-Form two linear equations based on the given information.
-Solve the simultaneous equations
-Write down the answer statement.
Idea of Functions
A function can be represented by
- a table
-ordered pairs
-a graph
-an equation
The function of y = mx+c, where m and c are contants, is called a
linear function.
The graph of y=mx+c is a straight line with gradient = m and yintercept = b.
Example(1)
Find the gradient of 3y= 5x + 8
Make y the subject of the equation
3y=5x+8
y=5/3x + 8/3
The gradient will be 5/3 which is the coefficient of x.
Gradient = rise/run
Equation of y-axis : x=0
Equation of x-axis : y=0
Coordinates = (x,y)
Properties of the Graph of the Quadratic function
y = ax + bx +c, where a is not 0

If it is positive (>0), it is a smiling curve.


If it is negative (<0), it is a crying curve.
If it is a smiling curve, it is minimum point.
If it is a crying curve, it is maximum point.
It cuts the x-axis at 0,1 or 2 points.
It cuts y-axis at only 1 point.
It has a vertical line of symmetry through its minimum point or
maximum point.
Eg: x = ____
Quadratic Equation
A quadratic equation can be simplified to the form ax + bx + c =0,
where a, b and c are the constants and a is not 0.
Solution by factorization
If ax + bx + c += 0 can be written as
(px+q)(rx+s)=0,
then x=-q/p or x=-s/r
Example (1):
Given 6x-4y/2x+3y = 2, find the value of x/y
6x-4y/2x+3y = 2
6x-4y = 4(2x+3y)
6x-4y = 4x+6y
6x-4x =6y+4y
2x=10y
2x/y=10
x/y=10/2=5
Example (2):
The sum of the squares of three consecutive positive off numbers is
251. Find the middle number.
(x) + (x+2) + (x+4) = 251
x+x+2(x)(2)+4+x+2(x)(4)+16 = 251
3x + 12x+ 20-251=0
3x + 12x 231 = 1
(3x-21)(x+11)=0
3x-21=0 or x+11=0
x=7 or x=-11(Rejected)
The middle number is (x+2)=7+2=9.
Pythagoras theorem
a + b = c

Hypotenuse (c)
Adjacent (b)

Opposite
(a)

The letter / number that is opposite the right angle is the hypo.
The corner of the triangle : Capital letter (A,B,C)
The side of the triangle : Small letter (a,b,c)
Diagonal = the line that cuts the square is the middle. (slanted)
Diameter = the line that cuts the square is the middle
(horicontal/vertical)
If it is a trapezium, draw a perpendicular line from the shorter
parallel line to longer parallel line.
Determination of Right-angles triangles
Normally, the length that is the longest, is the hypo. (c)
Example (1):

Correct working:
GK = 29 = 841
GK =29cm GH + HK = 20 + 21
=400 + 441
=841
(Converse of pyth. Thrm) GK = GH + HK
Therefore triangle GHK is a right-angled triangle

KH = 21cm

GH = 20cm